(untitled) (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
The use of electronic educational resources is becoming increasingly widespread in modern education systems. In this context, integrating modern electronic educational resources into geography instruction makes the learning process more effective, interactive, and up-to-date. This article is intended for 7th-grade geography teachers in general education schools, methodologists, and practicing educators. It highlights the relevance and importance of electronic educational resources — such as interactive maps, virtual globes, video lessons, and online testing platforms — in teaching geography. Particular attention is paid to the practice of conducting quick assessments using the “Plickers” application; the effectiveness of lessons utilizing Plickers is demonstrated through the results of experimental trials. The article provides over 20 ready-made test questions for 7th-grade geography, along with methodological recommendations for teachers. These materials can be utilized to effectively organize geography lessons.